Meta-analysis of omega-3 polyunsaturated fatty acids on immune functions and nutritional status of patients with colorectal cancer - Yue, Tinghui; Xiong, Kai; Deng, Jia; Hu, Wenting; Tan, Tianying; Li, Shuangshuang; Yang, Tao; Xiao, Tianbao (Frontiers in Nutrition, 2022)
The clinical significance of Omega-3 polyunsaturated fatty acids (PUFAs) in the management of patients with colorectal cancer (CRC) after radical resection, was assessed in this meta-analysis. A comprehensive search was conducted until the 10th of April 2022, on electronic databases such as EMBASE, PubMed, MEDLINE and Cochrane Library, China National Knowledge Infrastructure (CNKI), China Biomedical Database (CBM), Wanfang Electronic Database, and VIP Medical Information System (VIP). Randomized controlled trials (RCTs) of Omega-3 PUFAs and conventional nutritional or blank treatments were selected. The following were evaluated in the pooled analysis: immune function-related indices (including IgA, IgG, IgM, CD3+, CD4+, CD8+ and the ratio of CD4+/CD8+), nutritional status related indicators (including total protein [TP], albumin [ALB] and prealbumin [PA]), and their corresponding 95% confidence intervals (CI). Following that, We carried out heterogeneity detection, sensitivity analysis, contour-enhanced funnel plot detect possible publication bias, and meta-regression analysis. Accordingly, twenty studies were included with 1,613 patients (809 in the Omega-3 PUFAs group and 804 in the control group). The results of the pooled analysis showed that Omega-3 PUFAs markedly enhanced the humoral immune function indices (including IgA [SMD = 0.54, 95% CI: 0.10-0.99], IgM [SMD = 0.52, 95% CI: 0.05-0.99], IgG [SMD = 0.65, 95% CI: 0.47-0.84]), and T cell immune function indices (including CD3+ [SMD = 0.73, 95% CI: 0.54-0.92], CD4+ [SMD = 0.76, 95% CI: 0.53-0.98], and the ratio of CD4+/CD8+ [SMD = 0.66, 95% CI: 0.39-0.92]). At the same time, the CD8+ index was markedly reduced by Omega-3 PUFAs interventions (SMD = -0.28, 95% CI: -0.66-0.09); the pooled analysis also indicated that Omega-3 PUFAs markedly improved nutritional status indicators (including TP [SMD = 0.53, 95% CI: 0.17-0.88], ALB [SMD = 0.43, 95% CI: 0.15-0.70], PA [SMD = 0.46, 95% CI: 0.01-0.90]). According to meta-regression analysis, the covariates of the small sample effect affected the robustness and credibility of the CD4+ result. The results of this study suggest that Omega-3 PUFA should be used as a valid immunonutritional therapy/support for the remedy of patients with postoperative CRC. This meta-analysis protocol was registered in PROSPERO (no. CRD42021288487).